PELAKSANAAN PROGRAM PENGEMBANGAN PRODUKSI IKAN KOLAM OLEH DINAS PERIKANAN KABUPATEN KAMPAR 2010-2013 (STUDI KASUS DESA KOTO MESJID KECAMATAN XIII KOTO KAMPAR) - ", Usman; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research wish to see progress of remarkable potency which owned by Countryside of Koto Mosque to acceleration of development of area of[is effort fishery of pool and also make area of Minapolitan Provinsi Riau se as inwrought self-supporting Countryside. The countrysides really will be developed by as a countryside which go forward, self-supporting and its secure and prosperous people, so that can be made by example of to the other countryside in Provinsi Riau. Therefore all my me of importance ( holder stake ) relevant and related/relevant of development in the countryside obliged to take role inwroughtly and bersinergi, so that the countryside can really go forward, self-supporting and its secure and prosperous people. Concept this is such in fact with system innovate area to realize aspiration decentralize and area autonomy, and also countryside autonomy. Problem of becoming background execution of development of fish potency production had by Countryside of Koto Mosque. This research represent research qualitative, hence data collecting technique at this research is descriptive analysis. This research use kuesioner, documentation ( interview and observasi ) with informan key as information object in this research. Data type which is used in this research is primary data and of sekunder obtained through direct interview and observation with informan key, and also propagated kuesioner to responder at this research. Pursuant to result of conducted analysis to data- research data utilize to express and answer question at research related to execution of program development of pool fish production in Countryside of Koto Mosque, hence can be taken by conclusion that Countryside of Koto Mosque one of them most dominant potency is fish conducting potency which have been developed by society. .Key words : Development of pool in Koto Mosque, Program, observation.